PREVALENCE OF GRAM-POSITIVE BACTERIA IN JEDDAH, KINGDOM OF SAUDI ARABIA: STUDY OF ANTIMICROBIAL RESISTANCE PATTERNS AND MOLECULAR TYPING - N. R. HELMI; R. M. ZAMAN; M. M. ALY (International Journal of Pharma and Bio Sciences, 2013)
Constant surveillance of microbial pathogens is essential for combating infectious diseases which account for at least a quarter of all illnesses. This prospective study was designed to provide information on the incidence of Gram-positive bacterial infections in King Abdulaziz University Hospital (KAUH), Jeddah, Saudi Arabia. A total of 98 Gram-positive isolates were obtained and identified. Their antibiotic susceptibilities were documented against several antibiotics. All methicillin-resistant Staphylococcus aureus (MRSA) were examined for the existence of the Staphylococcus aureus specific gene and mecA gene by polymerase chain reaction. The most common individual isolates were staphylococci (62.2%) followed by enterococci (30%), then streptococci (0.05%). Twenty nine percent of the isolates were recovered from wounds and the highest incidence was in intensive care units (30.61%). Twenty percent of MRSA isolates were multidrug resistance. Glycopeptide resistances were detected in two isolates of Enterococcus faecium. All strains were sensitive to linezolid and tigycycline. Molecular technique found that all the isolates of MRSA had S. aureus specific gene and mecA gene. In conclusion, the incidence of resistance in Gram-positive cocci causing infections in KAUH is an increasing problem and molecular techniques using mecA gene can be used to detect MRSA.